Occupational Asthma - Szram, Joanna; Cullinan, Paul (Seminars in Respiratory and Critical Care Medicine, 2012)
Population-based studies suggest that one in 10 cases of new, recurrent, or deteriorating asthma in adulthood is related to the workplace environment. Nonspecific, irritant exposures at work can upset symptom control in pre-existing disease (work-exacerbated asthma); where disease arises de novo from the workplace (occupational asthma) it generally has an allergic basis, arising from airborne exposure to a sensitizing agent. Over 350 workplace substances have been identified as asthmagens; most are either proteins or highly reactive chemicals. The diagnosis of occupational asthma should be rapid but precise because definitive identification of the causative exposure provides the greatest opportunity for appropriate workplace adaptations and functional improvement. The majority of cases can be diagnosed through a combination of a careful history, appropriate immunology (where available), and the detection of work-related variability in measurements of lung function made serially at work and at home. Occupational asthma is a disease that is potentially preventable and often curable; positive outcomes are dependent more on changes in the workplace than on pharmacological therapy.
Keywords: asthma; occupation; work